Hybrid Approach to Treat Total Thoracic Aortic Aneurysm in a Patient Undergoing Emergency Surgery for Descending Aortic Rupture - Zeitani, Jacob; Mvondo, Charles Mve; Chiariello, Giovanni; Nardi, Paolo; Chiariello, Luigi (The Thoracic and Cardiovascular Surgeon, 2013)
Rupture of the descending aorta is a life-threatening complication requiring emergency intervention. The endovascular approach (TEVAR) has been recently introduced to treat the descending aorta in the emergency setting, resulting in better early postoperative outcome as compared with traditional surgery. However, when the pathology involves the aortic arch and ascending aorta, TEVAR alone cannot be performed, requiring an alternative approach. We describe a one-stage hybrid repair via midline sternotomy to treat rupture of the descending thoracic aortic segment in toto.
Keywords: aneurysm; aorta/aortic; aortic valve and root